2018
DOI: 10.29089/2017.17.00053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of smoking on cyanide, IL-2 and IFN-γ levels in saliva of smokers and nonsmokers

Abstract: I n t r o d u c t i o n : Tobacco use is widely spread throughout the world. Smoking has several adverse effects on human health ranging from minor health conditions to death. A i m : This study aimed to investigate effect of smoking on level of saliva cyanide, interleukin-2 (IL-2) and interferon-gamma (IFN-γ) among smokers compared to nonsmokers in the city of Ilam, Iran. M a t e r i a l a n d m e t h o d s : This study was carried out among two equal groups of smokers as cases and nonsmokers as controls (N =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
(28 reference statements)
1
2
0
Order By: Relevance
“…Another study reported similar findings of increased levels of salivary IL-1β in e-cig users [42]. The inflammatory mediator IFN-γ was increased in urine samples of e-cig users compared with nonusers, which was also seen in tobacco smokers [43]. Supporting the observations in our study, pro-inflammatory effects of e-cig condensate on human alveolar macrophages in vitro have been reported in another study [44].…”
Section: Discussionsupporting
confidence: 91%
“…Another study reported similar findings of increased levels of salivary IL-1β in e-cig users [42]. The inflammatory mediator IFN-γ was increased in urine samples of e-cig users compared with nonusers, which was also seen in tobacco smokers [43]. Supporting the observations in our study, pro-inflammatory effects of e-cig condensate on human alveolar macrophages in vitro have been reported in another study [44].…”
Section: Discussionsupporting
confidence: 91%
“…Cigarette smoke from traditional cigarettes induces an inflammatory response in a short period of addiction, which was manifested in our experiment by elevated concentration of INF-γ observed in traditional smokers. As indicated by the study of Rahimi et al (2018) , prolonging the time of exposure to tobacco smoke intensifies the immune system response, which indicates an increase in the concentration of subsequent proinflammatory cytokines (IL-2). This theory is confirmed by the positive correlation between the duration of smoking and the content of INF-γ in the unstimulated saliva of subjects ( Rahimi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…As indicated by the study of Rahimi et al (2018) , prolonging the time of exposure to tobacco smoke intensifies the immune system response, which indicates an increase in the concentration of subsequent proinflammatory cytokines (IL-2). This theory is confirmed by the positive correlation between the duration of smoking and the content of INF-γ in the unstimulated saliva of subjects ( Rahimi et al, 2018 ). In light of the evidence it appears that the boost of the immune system reaction is caused by components of cigarette smoke other than nicotine.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the concentrations of these cytokines increased with smoking duration. 144 Mokeem et al demonstrated significantly higher levels of pro-inflammatory IL-1β and IL-6 in the saliva of cigarette smokers. 145 It is worth mentioning that IL-1β in saliva is associated with active smoking, regardless of the number of cigarettes smoked, in contrast to the level of TNF-α, the concentration of which positively correlates with the number of cigarettes smoked daily.…”
Section: Effect Of Smoking On the Salivary Inflammationmentioning
confidence: 99%
“…Rahimi et al found a significant increase in the levels of interferon gamma (IFN-γ) and IL-2 in the saliva of smokers as compared to non-smokers. 144 Thus, CS mainly affects the balance of cytokines produced by Th cells. Importantly, the concentrations of these cytokines increased with smoking duration.…”
Section: Effect Of Smoking On the Salivary Inflammationmentioning
confidence: 99%